Teaching Narrative Structures to Students majoring in Pre-School and Primary Education - Canals-Botines, Mireia (Studi sulla Formazione/Open Journal of Education, 2020)
In the context of teaching English as a second language to young and very young learners, future teachers need to find indirect ways to teach. Narrative structures in children’s literature and short films could be some tools to develop creativeness in future teachers. This research paper is based on the methodology used to teach students, majoring in Pre-school and Primary Education, through narrative structures and their practical application. This study is designed to prove that teaching narrative structures is a very effective tool to develop English language teaching strategies for the above-mentioned students.